Africa in the 21th century: prospects and causes; effects on Arican States - Almeida, E. C. (JANUS.NET, e-journal of International Relations, 2013)
The Organization of African Unity (OAU) was founded on May 25, 1963, and aimed at unifying all African nations, recently independent as a result of their fight for independence; in July 2002 and upon a not-so-innocent proposal by Muammar Kadhafi, the OAU becomes the African Union in the Durban Convention. The new AU aimed and aims at political and economic integration of the African Member-states.